BROWN AND LEVINSON’S POLITENESS STRATEGIES IN THE FILM KURUNG WITHIN THE CONTEXT OF BUGIS-MAKASSAR CULTURAL VALUES - Fitriansal; Suriadi; Nilam Sari; Abdullah (LLDIKTI Wilayah X, 2025)
This research intends to scrutinize the politeness strategies in Very Zalman Ewa’s film Kurung, utilizing the theoretical framework of Brown and Levinson (1987). The focus of the analysis is directed toward the application of four politeness strategies: bald on record, positive politeness, negative politeness, and off-record, provided that they are linked to the socio-cultural values of the Bugis-Makassar society. The results indicate that these four strategies function adaptively according to the social context and power relations. The bald on record strategy is employed in hierarchical situations demanding firmness; positive politeness appears in contexts of solidarity and affection; negative politeness is utilized to maintain respectful distance; while off-record politeness reflects the wisdom of speech through implicit and metaphorical forms. These findings illustrate that politeness in Kurung is a reflection of the values of siri’ na pesse, malebbi, and lempu’—concepts which emphasize honor, empathy, and honesty in communication. Theoretically, this research extends the application of politeness theory into the local cultural context; practically, it has implications for cross-cultural pragmatic teaching; and culturally, it strengthens the position of language as a vehicle for inheriting human values and social harmony.